Analysis of Economic, Education, and Skill Factors against High Unemployment: A Case Study in West Java Province - Loso Judijanto; Didih Muhamad Sudi (Westscience Press, 2023)
This research investigates the intricate interplay between economic factors, education levels, workforce skills, and their impact on high unemployment rates, focusing on a case study in the West Java Province. Utilizing a quantitative approach, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze data collected from 187 participants. The measurement model's reliability and validity are assessed, and subsequent regression analyses explore the relationships between the identified constructs. The discriminant validity matrix ensures the distinctiveness of the constructs. Fit indices compare the Estimated Model with the Saturated Model, affirming the model's accuracy in capturing observed data. Noteworthy results highlight the significance of education and workforce skills in mitigating high unemployment. The research contributes to the existing literature by providing empirical insights into the multifaceted factors influencing unemployment in the specific context of West Java.